(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article proposes a discussion regarding the Highschool BNCC (National Common Curricular Base) structure, in order to analyze the general competence that sustain the documentation, based on the Philippe Perrenoud’s theory. This text is the result of the author’s post-doctorate degree research that has been used by Art teachers (Drama, Dance, Visual Arts or Music), with the main purpose being to help elaborate critical and strategic thinking as to deal with the BNCC, which is being implemented in all Brazilian states. The theory on which is currently being proposed towards a more in-depth reflection about the future of the Art discipline within the current political context.